MPOX A - GLOBAL PUBLIC HEALTH THREAT - Abraham, John; Agarwal, Krishna (International Journal of Pharma and Bio Sciences, 2026)
Mpox also known as monkeypox, is a zoonotic viral disease instigated by the Mpox virus, a double-stranded DNA virus related to smallpox. The disease typically presents with flu-like symptoms and a characteristic rash that progresses through distinct stages, including painful lesions and scabs. Two recognized clades, Clade I and Clade II, show regional prevalence in Central and East Africa, respectively, with varying severity and mortality rates. Efforts to combat Mpox include targeted vaccinations, such as MVA-BN and LC16, prioritized for high-risk groups and regions. Recent research advances have identified G-quadruplex structures within the viral genome, enabling more precise diagnostic tools using fluorescent probes. Countries have implemented diverse strategies to curb Mpox spread, including intensified screening of travelers, enhanced laboratory diagnostics, and public health campaigns. While nations like the Democratic Republic of Congo (DRC) face severe outbreaks, others such as Indonesia, China, and Kenya emphasize rigorous surveillance and border controls. The evolving epidemic highlights the critical need for international collaboration, rapid diagnostic innovation, and equitable vaccine distribution to mitigate the global impact of Mpox. This review on Mpox (formerly monkeypox) should comprehensively address its recent epidemiology, including global incident trends, outbreak hotspots, and the factors driving its spread and explore vaccination efforts, focusing on the efficacy and availability of smallpoxbased vaccines used against Mpox. Recent advancements in diagnostics, including novel detection methods like rapid molecular assays, should be highlighted. The review examines preventive measures undertaken by affected countries, such as contact tracing, isolation protocols, and public health campaigns.